2013
DOI: 10.1149/2.029311jes
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Mechanisms for Liquid-Air-Interface Corrosion of Steel in High Level Radioactive Waste Simulants

Abstract: Several hypothesized mechanisms of liquid-air-interface (LAI) corrosion in simplified simulants of high level liquid nuclear waste were investigated. The salt concentration cell theory is based on the possible development of an enhanced nitrate concentration or a depleted nitrite concentration in the meniscus solution compared to the bulk solution. In situ Raman spectroscopy was employed to monitor the time-dependent changes in nitrate concentration, nitrite concentration, and the nitrate-to-nitrite concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It has been reported that mild steels may be subjected to corrosion at the liquid-air interface (LAI) in high-level liquid radioactive waste, [1][2][3][4][5][6] although severe leaks due to this issue have not been reported yet. 6 The liquid radioactive waste is mainly alkaline, consisting of NaNO 2 , concentrated NaNO 3 and sometimes a relatively small amount of chloride.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that mild steels may be subjected to corrosion at the liquid-air interface (LAI) in high-level liquid radioactive waste, [1][2][3][4][5][6] although severe leaks due to this issue have not been reported yet. 6 The liquid radioactive waste is mainly alkaline, consisting of NaNO 2 , concentrated NaNO 3 and sometimes a relatively small amount of chloride.…”
mentioning
confidence: 99%
“…It has been reported that mild steels may be subjected to corrosion at the liquid-air interface (LAI) in high-level liquid radioactive waste, [1][2][3][4][5][6] although severe leaks due to this issue have not been reported yet. 6 The liquid radioactive waste is mainly alkaline, consisting of NaNO 2 , concentrated NaNO 3 and sometimes a relatively small amount of chloride. 1,[6][7][8][9][10][11] Nitrite has been reported to inhibit corrosion of alloys, [12][13][14][15][16] while nitrate was regarded as either a corrosion inhibitor [17][18][19][20][21][22] or an aggressive species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 is confirmed through the occurrence of a Raman band at 1325 cm −1 , due to the internal mode of NO 2 − , after the first regeneration step (2; Fig. 4B) (51). As in situ XRD (vide supra) did not evidence peaks due to crystalline NaNO 2 or Na 2 O, we postulate that ionic pairs of [Na + …NO 2 − ] and [2 Na + …O 2− ] (products of NaNO 3 decomposition) remained dissolved in the melt…”
Section: In Situ Raman Spectroscopy Coupled With Ms To Follow Na 2 Mg...mentioning
confidence: 80%
“…Literature reports that ALI corrosion can appear in pairs that do not show corrosion in fullysubmerged metal surfaces [28,29]. Although the mechanism of ALI corrosion is still not well understood [28,30,31], some authors relate it to the dissolved oxygen at the airliquid interface [32,33].…”
Section: Corrosion Measurementsmentioning
confidence: 99%